Gestational diabetes mellitus: the effects of diagnosis time and implementation of diabetic care on management of glycemia - Gruszka, Andrzej; Adamczyk-Gruszka, Olga; Lewandowska-Andruszuk, Izabela; Siennicka, Marzena; Gruszka, Jakub (Medical Studies/Studia Medyczne, 2014)
Introduction : Pregnancy is considered diabetogenic condition related to increased requirements for insulin, its increased secretion and ongoing insulin resistance. In pregnancy increased insulin secretion cannot compensate increased requirements which leads to gestational diabetes mellitus (GDM). If diagnosed too late or ill-treated diabetes can cause serious complications in the course of pregnancy and delivery as well as late complications in neonate. Aim of the research: To assess if time of diagnosis of gestational diabetes mellitus and implementation of diabetic care influence glycemia management and clinical condition of neonate after birth. Material and methods: The survey was carried out in the group of 300 pregnant women with GDM. The patients were divided into 3 groups: group A – patients with GDM diagnosed between 10–12 week hbd, group B – patients who had GDM diagnosed between 24–28 week hbd and group C – GDM diagnosed between 29 week hbd and delivery. Results: The analysis revealed correlation between the frequency of GDM and patient’s age and body mass index. Time of GDM diagnosis and following recommendations for GDM management depend on patient’s place of living and socio-economic status. Neonate’s condition is affected by proper glycemia management. Conclusions: There is a correlation between place of living, poor socio-economic status and managing glycemia, which should contribute to developing effective methods of care for women living in those areas. Patients’ body mass index significantly correlated with fetus macrosomy, which significantly affected the way pregnancy was terminated and neonate’s condition after birth. Time of GDM diagnosis has a big influence on glycemia management which is essential for mother’s and neonate’s health.